2020
DOI: 10.3390/pr8040412
|View full text |Cite
|
Sign up to set email alerts
|

Choline-Based Ionic Liquids-Incorporated IRMOF-1 for H2S/CH4 Capture: Insight from Molecular Dynamics Simulation

Abstract: The removal of H2S and CH4 from natural gas is crucial as H2S causes environmental contamination, corrodes the gas stream pipelines, and decreases the feedstock for industrial productions. Many scientific researches have shown that the metal-organic framework (MOF)/ionic liquids (ILs) have great potential as alternative adsorbents to capture H2S. In this work, molecular dynamics (MD) simulation was carried out to determine the stability of ILs/IRMOF-1 as well as to study the solubility of H2S and CH4 gases in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…This phenomenon can be explained by the "like dissolves like" principle, which means polar H 2 S is easier to dissolve into polar IL compared with CH 4 . 28 Ishak et al 88 Ma et al 90 prepared a novel metal-based IL, triethylamine hydrochloride copper chloride (Et 3 NHCl•CuCl 2 ), and compared the adsorption performance of H 2 S in pure zeolite, cyclodextrin-grafted zeolite (CDGZ), zeolite-supported IL (ILzeolite), and cyclodextrin-modified zeolite-supported IL (IL-CDGZ). The order of H 2 S removal capacity is CDGZ < zeolite < IL-zeolite < IL-CDGZ.…”
Section: Il-reinforced Adsorbents and Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon can be explained by the "like dissolves like" principle, which means polar H 2 S is easier to dissolve into polar IL compared with CH 4 . 28 Ishak et al 88 Ma et al 90 prepared a novel metal-based IL, triethylamine hydrochloride copper chloride (Et 3 NHCl•CuCl 2 ), and compared the adsorption performance of H 2 S in pure zeolite, cyclodextrin-grafted zeolite (CDGZ), zeolite-supported IL (ILzeolite), and cyclodextrin-modified zeolite-supported IL (IL-CDGZ). The order of H 2 S removal capacity is CDGZ < zeolite < IL-zeolite < IL-CDGZ.…”
Section: Il-reinforced Adsorbents and Membranesmentioning
confidence: 99%
“…This phenomenon can be explained by the “like dissolves like” principle, which means polar H 2 S is easier to dissolve into polar IL compared with CH 4 . Ishak et al compared the stability of choline (Chl)-based ILs/isoreticular MOF (IRMOF-1) composites with different anions of ILs, such as [SCN] − , [OTf] − , and methyl sulfate ([MeSO 4 ] − ). They found that a smaller-sized anion of IL contributed to a better stability since it could easily diffuse inside the pores of IRMOF-1.…”
Section: Ils and Dess For H2s Removalmentioning
confidence: 99%
“…Many great experimental and theoretical achievements have been made in developing well-performing IL/MOF composites in CO 2 /CH 4 or H 2 S/CH 4 separation. ,, However, the incorporated ILs are mainly present as the combination of imidazolium cations and inorganic anions. These ILs generally possess some toxicity, which is detrimental to the concept of environmental protection. ,, Therefore, new green and well-performing ILs should be introduced into MOFs to realize excellent natural gas purification.…”
Section: Introductionmentioning
confidence: 99%
“…The excellent absorption performance of choline-based amino acid ILs is mainly derived from their large polarity, where the functional groups (−COOH and −NH 2 ) of choline cations and amino acids anions (including alanine, [Ala]; glycine, [Gly]; serine, [Ser]) are expected to boost the intermolecular interactions. , Even though one cannot guarantee that incorporating this kind of ILs will lead to a satisfying separation result because the IL in confined pores may play different roles with the ILs in the bulk phase. For example, Xia et al found a reduced CO 2 uptake in [Emim]­[Gly]/UiO-66 because of the blocking effect, regardless of the good solubility of gases in bulk [Emim]­[Gly]. , However, to our best knowledge, the works that investigate the (CO 2 and H 2 S)/CH 4 separation performance of [Chl]­[AA] ILs/MOF composites are pretty scarce, , which cannot provide solid evidence to demonstrate that [Chl]­[AA] ILs could be good alternatives to the traditional imidazolium-based ILs in acid gas removal. Furthermore, some critical problems related to the IL/MOF composites still need to solve (1) how to trade off the effect of pore volumes and IL-MOF interaction on gas adsorption and (2) how to develop special IL/MOF composites with better adsorption capacity and selectivity.…”
Section: Introductionmentioning
confidence: 99%